EKPLORASI BENTUK LICHENES DENGAN TEKNIK DIGITAL PRINTING DAN LAMINASS PVC SEBAGAI DECORATIVE TRIMS PADA BUSANA BALL GOWN - Dea Indriani; Mila Karmila (Fesyen Perspektif, 2017)
Lichen (licheness) is a compound organism that is  a combination of  algae and Boletus (mushroom). Lichenes  is  symbiosis between algae or blue green algaewith fungi of the class Ascomycotina or Basiciomycotina thats structure affect the morphology of lichens. Lichens were widely spread on the surface of the Earth and are able to inhabit the extreme places, like the tundra, a very hard stone surfaces in the mountains or the beach. Based on its form lichens can be distinguished into three groups namely Krutos (like the crust), Folios (such as leaves), and fruktikos (like Bush).The uniqueness of the structure morphology and colour Lichenes have inspired writers to adapt into a dress ball gown as a decoration. Growing  fashion trend from time to time. The trend is predicted to have a theme 2017 as "Grey Zone" that has a sub theme that is Vigilant, Archean, Criptic,and Digitarian. sub theme has a characteristic and diverse characteristics in exploration. Archean is a theme inspired by the early period of the occurrence of fotosintesa in all, themes that represent the thoughts about the essence of life. Lichens are an inspiration is used as an exploration of the idea of shape and color in decoration dress ball gown with a touch of  laminated  PVC and sequins Pearl used as decoration Decorative Trims on the couture ball gown.